Notes on the reproduction of Kentropyx altamazonica(Squamata: Teiidae) andImantodes lentiferus(Serpentes: Dipsadidae) from southeast Peru - Serrano Rojas, Shirley Jennifer (2016)
Field observations on the reproductive biology of squamate reptiles are important to understanding the life history, ecology, and evolution of this diverse group (Vitt 1991, Ramírez-Bautista et al. 2000, Vittet al. 2001, Wernecket al. 2009); however, these data remain sparse for many tropical species (Figueroaet al. 2013, Sousaet al. 2014). Seasonality, clutch frequency, clutch size, egg size, and body size are important factors related to the life history of oviparous squamates (King 2000, Nelsonet al.2004, Kratochvíl and Frynta 2006a,b, Wanget al. 2011). Here, we present important information on the reproductive cycles of two, little-known Amazonian reptiles,Kentropyx altamazonica(Cope, 1876) andImantodes lentiferus(Cope, 1894). Neither species has been assessed by the International Union for Conservation of Nature (IUCN) Red List.